Role of Health Psychologist in physical, social and mental health development among school students - Wani, Mohammad Amin; Adam, Yousuf (International Journal of Psychosocial Rehabilitation, 2020)
Due to increase in occurrence of problematic behaviors like substance abuse, abnormal behaviors and illness related lifestyle, sedentary habits and disturbed social among school children and adolescent. It is necessary to implement School Based Student Centered Care (SBSCCThis paper aimed to emphasize the role of health Psychologist in student centered care and assess the self-esteem, perceived social support, resilience, internet addiction, and mental health of students. This study was carried one of private school with 92 students (38 Boys & 54 Girls) from Grade 12, and their mean age is 17+/-1. Rosenberg Self-esteem Scale, Multi-dimensional scale of perceived social support, Psychological Resilience Scale, Internet Addiction test and mental health inventory-38 along with measure of body mass index were used for measurementthe finding highlights the students self esteem, social support, resilience, addiction to internet, and mental health. Further models on person or patient centered care, role of Health Psychologist in school based student centered care, and school based student centered care (SBSCC) in coordination with students, teachers and parents are also highlighted in the study.